Exploration of Making Perfume based on Extracts of Pandan Wangi (Pandanus amaryllifolius), Lemongrass (Cymbopogon citratus) and Orange Leaves (Citrus hystrix): Natural Aroma Innovation - Putri Faradilla; Moondra Zubir; Ani Sutiani; Dinda Dwi Hasanah; Dian Finensia Saragih; Putri Rahmayani; Tesa Juliana Br.Samosir (Universitas Negeri Medan, 2025)
Perfume is a familiar product used in daily life, as a necessity to appear confident. Natural perfume is currently an essential use such as the use of panda, lemongrass and orange leaf extracts because the use of plants as basic perfume ingredients is safe and has minor side effects. This research aims to make a perfume that is durable, safe to use and low in alcohol content. The method used is the extract filtration method and then organoleptic test, alcohol content test and pH test. From the research conducted, perfume with pandanus extract has a longer lasting fragrance and is safe to use.